Kayardild morphology and syntax - Round, Erich R. (Oxford : Oxford University Press, 2013)
Presenting new data and analyses of the inflectional system and syntax of Kayardild, a typologically striking language of Australia, this book makes Kayardild accessible to mainstream formal linguistic theory and so will appeal to a broad new audience as well as to those who know Kayardild well.
Series from CIP print record.
Description based on online resource; title from home page (viewed on Dec. 14, 2012).
Includes bibliographical references and index.
Keywords: Gayardilt language -- Morphology; Gayardilt language -- Syntax